Speeches of university youth on health politics with the LGBTQIA+ population through web seminars (Research, Society and Development, 2021)
Digital Information and Communication Technologies have made it possible to teach in schools and universities due to the health restrictions caused by the Covid-19 pandemic. However, the online channel, Web Radio AJIR, which accounts for 13 years of foundation with experiences in the production of communication with young people through programs, web classes, web seminars, online courses and among other pedagogical strategies for the promotion of educational web care in health even before the pandemic, has been strengthened by expanding its devices of knowledge in professional training in health. Thus, the objective of this study was to analyze discourses of university youth mediated in the dialogical productions of web seminars about the LGBTQIA+ population, developed in the discipline of Policies and Knowledge in Collective Health in the undergraduate nursing course. This research was characterized as documentary, descriptive and qualitative, with the participation of 56 young people who produced questions-discourses denoting gaps in these contents in professional training and practice in everyday direct care in the Unified Health System, being requested more content on health care for the population that claims equity, completeness and universal access to care in health services as a human right. It was concluded that when addressing equity policies with university students, it awakened the understanding of expanded care and the use of digital communication technologies as producers of web care practices, in addition to considering life stories, singularities, respect for sexual and gender diversity, and the human dignity of LGBTQIA+ people.